خبر واحد کے ذریعے قرآن کریم کی تخصیص کا معنی پر اثر- جمہور فقہاء کرام کے اقوال کا تحقیقی مطالعہ: Exclusion'sEffect on Meaning from Generalized and Holy Text by Hadith which is not continual- A Research Based Study of the Majority of Jurists Views - Husain , Sanaullah (FIKR-O NAZAR فکر ونظر, 2024)
Khabar wahid (خبر واحد) is a type of Hadith (prophet's saying). It is not a continual one (متواتر) and not multi narrated. Some time there is some exclusion in khabar wahid from general text of the Holy Qur’an. Different opinions are available about such specification or Exclusion. According to one opinion it is allowed to make some exclusion from holy text by Khabar wahid while the other opposed it, because of probability that it may not be words of Prophet or some other reasons. Followers of Sunnah also have two opinions, Majority of Scholars who are consist on Malik bin Anas, Mohammad bin Idrees Al Shafi and Ahmand bin al Hanbal make exclusion by khabar wahid with the condition that it must be correct and sound (one which has a continuous chain of narrator, each narrator having met the one he narrated from, and in which each narrator is known to righteous and to have a good memory). They also assists it with the evidence that consensus of the holy prophet's companion is also exist on such issues and the other group also accepted its application in some issues with the consideration that it was famous during the age of tabeen (generation of scholars and jurisprudents who had met only the prophet's companions and learnt from them). Abo Hanifah viewed that if it is not famous during the age of tabeen then it is abrogation of the holy quran by the Khabar Wahid which is too little in rank as compared to the holy text that is why it is not allowed.